دور الموارد البشرية وانعكاسها على القطاع الفندقي: بحث تطبيقي لآراء عينه من العاملين الاداريين في عدد من المنظمات الفندقية في بغداد - ميثم حميد ناصر (PROSPECTIVE RESEARCHES, 2023)
The current research aims to investigate the possibility of (the impact of human resources and their effectiveness on tourism), by presenting the problem and then the importance of tourist hotels (the city of Baghdad), and trying to research the latest developments in the field of study with standing on the essential ideas related to the current variables (human resources, tourism). And then trying to come up with a set of recommendations that contribute to strengthening the practice and adoption of the study variables. And based on the importance of the subject for the study sample and its members and because of its fundamental impact on their activities, the study adopted the exploratory analytical method, as the study population included (5) tourist hotels that have a good reputation among the tourist hotels in the tourism work, while the sample was composed of (90) director distributors. In administrative levels with a degree (members of the board of directors, the managing director, directors of departments), and the study used the questionnaire as a main tool for data collection and information, as well as personal interviews. The study found the most prominent results that showed the correctness of the most important hypotheses (the high level of the main study variables in the studied hotels, the presence of moral correlation between them and the presence of a moral impact of human resources in the tourism), and that this effect increases with their presence together and these results were identical with the assumptions in this aspect On this basis, the study came out with a set of recommendations, the most important of which is the interest in the scientific tourism departments in universities and hotel and tourism institutes and their development in line with the labor market and a plan for the development of tourism in Iraq.